Solute transport in aquifers of arbitrary variability: A time‐domain random walk formulation. Issue 7 (12th July 2014) - Cvetkovic, Vladimir; Fiori, Aldo; Dagan, Gedeon
Abstract Solute transport in three‐dimensional aquifers, with spatially varying hydraulic conductivity of arbitrary point distribution is investigated. The basis of our study is a multiindicator model (MIM) representation of the heterogeneity, combined with a self‐consistent approximation for groundwater flow and particle transport. A time‐domain random walk (TDRW) approach is presented for computing the expected mass arrival along the longitudinal transport direction that is simple and honors the hydrodynamics of flow for any variability. Using hydraulic conductivity measurements at the MADE site and the MIM, it is shown that the travel time distribution for large variability, cannot be well reproduced by the common distributions used for modeling hydrological transport, such as the log‐normal distribution, or the inverse‐Gaussian distribution. The proposed TDRW approach directly relates to the Lagrangian trajectory formulation and is appropriate for applications where occurrence of negative flow velocities is small. These results open new possibilities for modeling solute transport in aquifers of arbitrary variability by the time‐domain random walk that can readily account for a wide range of mass transfer reactions.